2010
DOI: 10.1038/ki.2010.14
|View full text |Cite
|
Sign up to set email alerts
|

Age and comorbidity may explain the paradoxical association of an early dialysis start with poor survival

Abstract: Starting patients on dialysis early has been increasing in incidence in several countries. However, some studies have questioned its utility, finding a counter-intuitive effect of increased mortality when dialysis was started at a higher estimated glomerular filtration rate (eGFR). To examine this issue in more detail we measured mortality hazard ratios associated with Modification of Diet in Renal Disease eGFR at dialysis initiation for 11,685 patients from the French REIN Registry, with sequential adjustment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
101
4
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 141 publications
(115 citation statements)
references
References 24 publications
(48 reference statements)
8
101
4
2
Order By: Relevance
“…4,[17][18][19] Consistent with our finding that only 7% indicated that the planned start was never delayed, a possible explanation for these differences may be that the actual start usually is later than the planned start.…”
Section: Most Frequently Mentioned Reasons As Basis For Opinion (% Ofsupporting
confidence: 85%
See 2 more Smart Citations
“…4,[17][18][19] Consistent with our finding that only 7% indicated that the planned start was never delayed, a possible explanation for these differences may be that the actual start usually is later than the planned start.…”
Section: Most Frequently Mentioned Reasons As Basis For Opinion (% Ofsupporting
confidence: 85%
“…Results from Lassalle et al 19 also showed higher percentages of older patients and diabetes and cardiovascular diseases in patients starting at eGFR Ͼ10 mL/min/1.73 m 2 . Similar results were found by Abbreviations: CI, confidence interval; eGFR, estimated glomerular filtration rate; RRT, renal replacement therapy.…”
Section: Most Frequently Mentioned Reasons As Basis For Opinion (% Ofmentioning
confidence: 88%
See 1 more Smart Citation
“…The main concern of observational studies including ours is the difference between the clinical characteristics and dialysis indications of the early and late initiation groups. Patients with early dialysis initiation were more likely to be men and diabetic, have severe heart failure or coronary heart disease, are less likely to have glomerulonephritis or polycystic kidney disease and have lower serum albumin level and more comorbidity and in summary, they are sicker patients [5,9,14,17]. In our DAGL patients, we found similar results.…”
Section: Discussionsupporting
confidence: 78%
“…Data from the US Renal Data System (USRDS) between 1996 and 2008 showed that the proportion of patients initiating hemodialysis (HD) with an estimated GFR (eGFR) >10 mL/min/ 1.73m 2 increased from 20 to 52% and those with a starting eGFR of ≥15 mL/min/1.73m 2 increased from 4 to 17% [5,6]. Interestingly, most of the recent observational trials and a landmark randomized controlled trial failed to show a survival benefit of early initiation of dialysis in CKD patients [5,[7][8][9][10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%